Africa-Europe Cooperation and Digital Transformation - Daniels, Chux; Erforth, Benedikt; Teevan, Chloe (Innovations in International Affairs, 2023)
Africa-Europe Cooperation and Digital Transformation explores the opportunities and challenges for cooperation between Africa and Europe in the digital sphere. Digitalisation and digital technologies are not only essential for building competitive and dynamic economies; they transform societies, pose immense challenges for policymakers, and increasingly play a pivotal role in global power relations. Digital transformations have had catalytic effects on African and European governance, economies, and societies, and will continue to do so. The COVID-19 pandemic has already accelerated the penetration of digital tools all over the globe and is likely to be perceived as a critical juncture in how and to what purpose the world accepts and uses new and emerging technologies. This book offers a holistic analysis of how Africa and Europe can manage and harness digital transformation as partners in a globalised world. The authors shed light on issues ranging from economic growth, youth employment, and gender, to regulatory frameworks, business environments, entrepreneurship, and interest-driven power politics. They add much-needed perspectives to the debates that shape the two continents' digital transformation and innovation environments. This book will interest practitioners working in the areas of innovation, digital technologies, and digital entrepreneurship, as well as students and scholars of international relations. It will also be relevant for policymakers, regulators, decision-makers, and leaders in Africa and Europe.